ESTUDIO SOBRE LA FORMACIÓN PROFESIONAL Y OCUPACIONAL JUVENIL EN CONTEXTOS DE VIOLENCIA EN TIBÚ, COLOMBIA - Tarazona, Jairo Gelvez; Lacárcel, Alfonso Conde; Reché, Jose María Sola (European Scientific Journal, ESJ, 2015)
The present article shows the results of a research thesis aims at analyzing the impact of occupational and vocational training among the youth of the municipality of Tibú, Colombia, in a context of violence and marginalization. For this it has conducted a mixed design descriptive research using two questionnaires created for that purpose (one for teachers and one for students), well as a number of interviews in order to contrast the information obtained. The results showed the need to continue encouraging and supporting educational processes, teachers and institutions and families and address the particular impact of socio-economic aspects, values, beliefs, reality of the area in which are found the Youth of this region to promote an effective and stable change in the social, personal, professional and empowering a culture of peace and coexistence climate.